Comparison of Chloroxylenol 4.8% and Povidone Iodine 7.5% on Total Bacteria Count Post WHO Routine Hand Washing on Clinical Students at the Department of Oral Surgery, Faculty of Dentistry, Universitas Sumatera Utara March-May 2018 - Ahyar Riza; Isnandar Isnandar; Rahmi Syaflida; Jasmine Jasmine (Journal of Dentomaxillofacial Science, 2019)
Objective: To compare Chloroxylenol 4.8% and Povidone Iodine 7.5% on total bacterial count post WHO routine hand washing on clinical students at the department of oral surgery, Faculty of Dentistry, Universitas Sumatera UtaraMaterial andÂ  Methods: This was an experimental study with post-test only control group design approach. Purposive technique is applied to collect samples which are clinical students. In this study, sample were divided into 3 groups and each consisting of 10 people. Aquadest was used as control group while Chloroxylenol 4.8% and Povidone Iodine 7.5% was used as the treatment group. Each member performed routine handwashing using WHO method for 1 minute long.Results: The results were statistically analyzed using Kruskal Wallis and Mann-Whitney Test. The comparison between Chloroxylenol and Povidone Iodine showed no significant difference to the total bacteria count after handwashing (p>0.05) but the Chloroxylenol group showed a greater mean reduction.Conclusion: Chloroxylenol and Povidone Iodine are capable reducing the number of bacteria in hands, therefore it can be a good antiseptic choice for hand washing.